Italy : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Italy. (IMF Staff Country Reports; Country Report ;, 2021)
The pandemic dealt a severe blow to the Italian people and their economy. GDP fell by nearly 9 percent in 2020, with much larger drops for contact-intensive services. Public and corporate debt increased strongly and preexisting vulnerabilities have likely worsened. The government is prioritizing resolving the health emergency and transforming the economy to lift productivity, improve social outcomes and strengthen resilience to future shocks and structural change. The large National Recovery and Resilience Plan-partly financed by sizable Next Generation EU resources-will be used to increase physical and social infrastructure. Outlook. GDP is expected to recover strongly in 2021-22 and to grow well-above trend over the medium term, supported by investment spending. Nonetheless, economic scarring could be sizable. The two-sided risks relate to how the pandemic progresses, the efficiency of investment spending and the extent of savings drawdown, with large costs associated with the downside.